Implementation of Digital Teaching Material Containing Local Wisdom Values for Strengthening Pancasila Student Profile Project (P5) of Independent Curriculum in Social Studies Learning - Mina Holilah; Muhammad Nur; Retno Ayu Hardianti; Qori Aulia (Universitas Lambung Mangkurat, 2024)
The Strengthening Pancasila Student Profile (P5) project is one of the main programs developed by the government in the Merdeka curriculum at the school level. This policy needs to be responded to positively to achieve the expected Pancasila Student Profile. P5 is a number of character traits and competencies of students which are based on the values of Pancasila including an attitude of faith, devotion to God Almighty, noble character, global diversity, independence, mutual cooperation, critical reasoning and creativity. This research focuses on the implementation the development of digital teaching materials containing local wisdom in P5 as an effort to support the successful achievement of the Pancasila Student Profile in the Independent Curriculum which is full of the values of Pancasila based on the characteristics of educational units in Bandung. The research method used is descriptive quantitative with questionnaires and interviews involving social studies teachers in Bandung as a life curriculum in the field implementing the Merdeka Curriculum. The research results show that P5 in Greater Bandung has been running well through various project model strategies, inserting local wisdom values typical of the area around the school, and utilizing digital teaching materials as a supporting tool.